2014
DOI: 10.1186/1472-6831-14-58
|View full text |Cite
|
Sign up to set email alerts
|

Sealing versus partial caries removal in primary molars: a randomized clinical trial

Abstract: BackgroundThe resin-based pit and fissure sealant is considered a successful tool in caries prevention, however there is a growing evidence of its use in controlling already established caries in posterior teeth. The aim of this clinical trial is to verify the efficacy of pit and fissure sealants in arresting dentinal caries lesions compared to partial excavation and restorative treatment in primary molar teeth.MethodsThirty six patients with occlusal cavitated primary molar reaching outer half of dentin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
44

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 31 publications
2
61
1
44
Order By: Relevance
“…After 2-3 years, the authors observed that 9 out of a total of 10 failures were related to the clinical performance of the sealants: 7 cases showed loss of retention and 2 cases showed partial retention (annual failure rate of resin sealants of 7.4%). Similarly, Hesse et al 11 showed that all the failures detected in sealants placed in primary molars were clinical failures, resulting in a higher frequency of retreatments in this group. Collectively, these findings indicate that the use of dental sealants to control caries lesions requires patient compliance in attending regular follow-ups to assess the need for retreatment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…After 2-3 years, the authors observed that 9 out of a total of 10 failures were related to the clinical performance of the sealants: 7 cases showed loss of retention and 2 cases showed partial retention (annual failure rate of resin sealants of 7.4%). Similarly, Hesse et al 11 showed that all the failures detected in sealants placed in primary molars were clinical failures, resulting in a higher frequency of retreatments in this group. Collectively, these findings indicate that the use of dental sealants to control caries lesions requires patient compliance in attending regular follow-ups to assess the need for retreatment.…”
Section: Discussionmentioning
confidence: 73%
“…In primary molars, one study comparing sealing versus partial caries removal showed that both strategies had similar efficacy in arresting the caries progression of cavitated occlusal lesions. 11 However, the authors found a higher clinical survival rate at 18 months for restorations, with a higher frequency of retreatments in the sealant group. More randomized controlled clinical trials are needed to investigate whether the placement of a sealant may be seen as a clinical alternative to control caries progression in lesions with shallow-to-moderate depth.…”
Section: Introductionmentioning
confidence: 89%
“…In this method, preparation of the cavity is limited to the minimal removal of the decayed tissue, the cavity then being restored with composite resin or glass ionomer cement before sealant is applied along the edges of the filled cavity, covering the entire occlusal surface 30 . However, given the various difficulties in managing children's behavior during conventional restorative therapy, sealing carious dentin lesions in deciduous teeth could be an interesting and less invasive option 8 . Some restorative materials used to seal carious lesions of the oral environment are reported to have cariostatic properties, guaranteeing reductions in the number of microorganisms and inducing structural alterations to the dentin, which leads to arrestment of the lesions.…”
Section: Therapeutic Approaches To Cavitated Carious Lesions In Decidmentioning
confidence: 99%
“…However, there is growing evidence of their effectiveness in controlling caries already established in posterior teeth 8 and the recommendation for the application of occlusal sealants seems to be changing from primary prevention to Strategies for control and treatment of carious lesions in deciduous molars: a review of the literature to pulp exposure and, consequently, more invasive and complex procedures, such as direct pulp capping, pulp curettage and pulpotomy, which may trigger a series of reinterventions that could culminate in the premature extraction of teeth 40 .…”
Section: Sealing Carious Lesionsmentioning
confidence: 99%
See 1 more Smart Citation